Netralitas ASN dalam Pemilukada Luwu Utara Tahun 2020 - Suharto, Suharto; Sahlania, Onno; Bachtiar, Bachtiar (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2023)
The Study's objective in the Regency North Luwu 2020 Regional Election, Apparatus State Civil Service (ASN) is used for know-neutrality purposes. This qualitative research study aims to investigate instances of ASN violations against regulation neutrality in the Election General Regional Head (Pimilukada). It will do this by means of observations and in-depth interviews with representative managers of party politics in the District North Luwu, as well as with candidate regional heads who are third partners and who have a track record of team success and who competed in the regional election in the Regency North Luwu 2020. Results of the research indicate that there is no impartial apparatus state civil servant; instead, the most frequent occurrence is on activity campaigns. These campaigns involve Apparatus State Civil Servants, who attend activity declarations, offer open support via social media, and even assist in the installation of billboard candidate pairs in the region, particularly apparatus at the subdistrict level. Then, under the guise of sharing inexpensive foods in a manner that resembled that of packing, ASN engaged the public in mobilisation. In addition, a civil apparatus working in the capacity of a figure society invited the candidate pair to the region so they could socialise. On the other hand, ASN uses government-owned vehicles as well as buildings and spaces to provide the majority of facilities. It is possible to prove many ASN violations in the 2020 regional election.